The Eastern Arab Christians Between the European Spreading Influence and Ideological Hegemony - Jasim, Haidar (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The study was divided into three axes: the first is a preliminary entitled “The historical roots to form the issue of minorities” with a summary of its conditions until the stage of its submission to the authority of Islam. The second axis carried the title "Christian denominations in the Ottoman era" and focuses on the Ottoman policy towards Christians. The third axis addressed the development of the conditions of Christians during the beginning of the emergence of Arab countries and the treatments set by the Arab regimes for the state of separation in legal legislation towards them.